Uncertainty in Historical Land-Use Reconstructions with Topographic Maps - Kaim, Dominik; Kozak, Jacek; Ostafin, Krzysztof; Dobosz, Monika; Ostapowicz, Katarzyna; Kolecka, Natalia; Gimmi, Urs (Quaestiones geographicae, 2014)
The paper presents the outcomes of the uncertainty investigation of a long-term forest cover change analysis in the Polish Carpathians (nearly 20,000 km ) and Swiss Alps (nearly 10,000 km ) based on topographic maps. Following Leyk et al. (2005) all possible uncertainties are grouped into three domains - production-oriented, transformation- oriented and application-oriented. We show typical examples for each uncertainty domain, encountered during the forest cover change analysis and discuss consequences for change detection. Finally, a proposal for reliability assessment is presented.